Jus post bellum and transitional justice - May, Larry; Edenberg, Elizabeth (New York : Cambridge University Press, 2013)
'This collection of essays brings together jus post bellum and transitional justice theorists to explore the legal and moral questions that arise at the end of war and in the transition to less oppressive regimes. Transitional justice and jus post bellum share in common many concepts that will be explored in this volume. In both transitional justice and jus post bellum, retribution is crucial. In some contexts criminal trials will need to be held, and in others truth commissions and other hybrid trials will be considered more appropriate means for securing some form of retribution. But there is a difference between how jus post bellum is conceptualized, where the key is securing peace, and transitional justice, where the key is often greater democratization. This collection of essays highlights both the overlap and the differences between these emerging bodies of scholarship and incipient law'--
1. Just military occupation? A case study of the American occupation of Japan / Shunzo Majima -- 2. Was damals Recht war... Nulla Poena and the prosecution of crimes against humanity in occupied Germany / Lawrence Douglas -- 3. Community based accountability in Afghanistan: recommendations to balance the interests of justice / Michael A. Newton -- 4. (Re)defining crimes against humanity for a jus post bellum world / Charles Chernor Jalloh -- 5. Jus post Bellum and Amnesties / Max Pensky -- 6. Earthquakes and wars: the logic of international reparations / Gabriella Blum and Natalie J. Lockwood -- 7. International criminal court, the trust fund for victims and victim participation / Jovana Davidovic -- 8. Truthfulness in transition: the value of insisting on experiential adequacy / Cindy Holder -- 9. Nunca Mas: truth commissions, prevention, and human rights culture / Margaret Urban Walker -- 10. Transnationalizing peacebuilding: transitional justice as a deliberative process / James Bohman -- 11. Jus Post Bellum and political reconciliation / Colleen Murphy and Linda Radzick.
Includes bibliographical references and index.
Keywords: Peace-building -- Law and legislation; Postwar reconstruction -- Law and legislation; International criminal law; Restorative justice; War reparations